Visions of the holy: studies in biblical theology and literature - Sweeney, Marvin A. (Resources for biblical study, 2023)
"This collection of previously published and unpublished essays by Marvin A. Sweeney examines issues in biblical and postbiblical theology. Topics include the canonical understanding of the Tanak, the character of Jewish biblical theology, Asian biblical theology, the understanding of Shabbat, intertextuality in Exodus-Numbers, Samuel, Isaiah, and the Twelve in intertextual perspective, and the democratization of messianism in modern Jewish thought. The volume represents a lifetime of study of the Hebrew Bible in one volume for scholars, students, and clergy interested in theological readings of the Hebrew Bible"--